2020
DOI: 10.1002/jcla.23400
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA T‐cell factor 7 in multiple myeloma: A potential biomarker for deteriorated clinical features and poor prognosis

Abstract: Background This study aimed to investigate the correlation of long non‐coding RNA T‐cell factor 7 (lnc‐TCF7) with clinical features and prognosis in patients with multiple myeloma (MM). Methods Totally, 216 newly diagnosed symptomatic MM patients and 60 healthy controls (HCs) were enrolled. Bone marrow samples were collected from patients before treatment and from HCs on donation to detect lnc‐TCF7 expression in plasma cells by reverse transcription quantitative polymerase chain reaction. Besides, clinical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Among previously reported lncRNAs, lncRNA T-cell factor 7 (lnc-TCF7) serves as a vital oncogene, which contributes to malignant behaviors and cancer stemness in several carcinomas, such as non-small cell lung, colorectal and liver cancers (7)(8)(9)(10). Besides, lnc-TCF7 exhibits potency as a prognostic marker reflecting advanced tumor stages and worse survival in some carcinomas (11)(12)(13). However, no previous studies have been performed on the function and mechanism of lnc-TCF7 in EOC, as well as its clinical value for EOC prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among previously reported lncRNAs, lncRNA T-cell factor 7 (lnc-TCF7) serves as a vital oncogene, which contributes to malignant behaviors and cancer stemness in several carcinomas, such as non-small cell lung, colorectal and liver cancers (7)(8)(9)(10). Besides, lnc-TCF7 exhibits potency as a prognostic marker reflecting advanced tumor stages and worse survival in some carcinomas (11)(12)(13). However, no previous studies have been performed on the function and mechanism of lnc-TCF7 in EOC, as well as its clinical value for EOC prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, our fndings revealed that MM patients with high MIR17HG expression had signifcantly shorter PFS and OS than those with low MIR17HG expression. In light of the fact that MIR17HG is associated with higher Scr, LDH levels, and more advanced clinical stages, which are associated with poorer survival of MM patients [36], it is not difcult to infer that the high MIR17HG expression is associated with adverse survival of MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of the cytoplasmic circular lncRNA Circ_0000190, MEG3 and PRAL has been associated with better PFS and OS, and high expression levels of SMILO (specific myeloma intergenic long non-coding RNA) with better OS in MM patients [ 13 , 36 , 72 , 86 , 87 ]. By contrast, high expression levels of lnc-TCF7 , MALAT1 , MIAT , NEAT1 and PDLIM1P4 have been associated with worse PFS and OS in MM patients [ 13 , 61 , 63 , 70 , 75 , 76 , 77 , 80 ], the overexpression of CRNDE , LINC00152 , LINC00461 , LINC01234 , lnc-ANGPTL1-3 , PDIA3P and UCA1 with worse OS, and the overexpression of ENSG00000254343 , H19 and NR_046683 (also known as ST3GAL6-AS1 , ST3GAL6 antisense RNA 1) with worse PFS in MM patients [ 13 , 40 , 46 , 56 , 85 , 93 , 95 ]. In addition, high expression levels of LUCAT1 were associated with worse five-year survival rates [ 62 ], and MM patients with the lncRNA BM742401 methylated showed worse OS than those patients with unmethylated BM742401 [ 35 ].…”
Section: Lncrnas As Biomarkers For Clinical Stratification Of MM Patientsmentioning
confidence: 99%